206k views
16 votes
How do you write y - 3 -
(x + 4) in slope intercept form?

User Nhi
by
5.3k points

2 Answers

3 votes
In slope-intercept form y - 5 = 3(x - 4) is y = 3x - 7.
User Fredmat
by
4.8k points
7 votes

Answer:

y = x + 7

Explanation:

Your original equation was:

y - 3 = (x+4)

First distribute

= (x+4)

Since there is no a value, then there is an invisible one and your result is:

y - 3 = x + 4

Then add 3 to both sides to get:

y = x +4 +3

y = x + 7


Since the slope-intercept form of a line is y = mx + b

where m is the slope and b is the intercept, then your equation is now in slope-intercept form.

Hope this helps! =D

User Yinqiu
by
5.4k points